The philosophy of criminal law selected essays - Husak, Douglas N., 1948- (Oxford : Oxford University Press, 2010)
This volume collects 17 of Douglas Husak's influential essays in criminal law theory. The essays span Husak's original and provocative contributions to the central topics in the field, including the grounds of criminal liability, relative culpability, the role of defences, and the justification of punishment.
Includes bibliographical references and index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal law -- Philosophy